Women's Experiences Regarding Physical Activity during the Postpartum Period: A Feminist Poststructuralist Study - Neda Akbari-Nassaji; Megan Aston; Jean Hughes; Christine Cassidy; Britney Benoit (MDPI AG, 2023)
Although recovery after birth can be promoted through bodily movement, many women do not engage in regular postpartum physical activity. While research studies have identified some of the reasons behind their decisions, including a lack of time, only a limited number of studies have been carried out to explore how postpartum physical activity is socially and institutionally constructed. Thus, the present study aimed to investigate the experiences of women regarding postpartum physical activity in Nova Scotia. Six postpartum mothers participated in semi-structured, virtual, in-depth interviews. Women's experiences of postpartum physical activity were examined through a discourse analysis guided by feminist poststructuralism. The following themes were identified: (a) socialization in different ways; (b) social support; (c) mental and emotional health; and (d) being a good role model for their children. The findings indicated that all women perceived postpartum exercise as a positive behavior that can promote mental health, although some postpartum mothers experienced social isolation and a lack of support. Furthermore, social discourses about motherhood caused the personal needs of mothers to be disregarded. The results showed that collaboration among health care providers, mothers, investigators, and community groups is necessary to promote and support mothers' engagement in postpartum physical activity.